2014
DOI: 10.1177/000313481408000819
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia in the Emergency Department: A Missed Opportunity

Abstract: Primary hyperparathyroidism is surgically correctable and frequently presents with mild hypercalcemia. The symptoms of hyperparathyroidism are nonspecific often leading to a delay in diagnosis until patients present with an acute condition. Literature suggests that up to 20 per cent of patients presenting to the emergency department (ED) found to have hypercalcemia are ultimately diagnosed with hyperparathyroidism. We performed a retrospective review from 2012 to 2013 of patients with hypercalcemia in our ED a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In a recent study, the cause of mild hypercalcaemia was only identified in 21% of patients [ 22 ]. In addition, only the minority of patients had a follow up or workup plan at discharge [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, the cause of mild hypercalcaemia was only identified in 21% of patients [ 22 ]. In addition, only the minority of patients had a follow up or workup plan at discharge [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the cause of mild hypercalcaemia was only identified in 21% of patients [ 22 ]. In addition, only the minority of patients had a follow up or workup plan at discharge [ 22 ]. In contrast, the vast majority of these patients, symptoms related to hypercalcaemia could be found [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation